A Study on Depth Sizing for Surface Cracks in KTX Brake Disc Using Rayleigh Wave - Yun-Taek Yeom; Min-Soo Kim; Hak-Joon Kim; Sung-Jin Song; Ho-Yong Lee; Sung-Duk Kwon; Sung-Sik Kang; Deok-Yong Sung (Advances in Materials Science and Engineering)
Korea Train eXpress (KTX), high-speed railway system, provides an important platform for public transportation and connects major metropolitans in Korea. KTX aiming towards next-generation transportation system has plans to increase the operation times. However, with increasing operation times, safety and reliability of the railways especially inspection of brakes systems becomes important. Therefore, in this study, a KTX brake disc inspection system using the Rayleigh wave is developed to characterize the cracks in the discs. The performance of the inspection system is evaluated on the KTX brake discs specimen having fabricated cracks as well as natural cracks. The result shows that the proposed algorithm successfully characterizes the crack types and estimated the length, width, depths and gap between cracks with good accuracy.